Comparison of physiological uptake of normal tissues in patients with cancer using 18F-FAPI-04 and 18F-FAPI-42 PET/CT - Mu, Xingyu; Huang, Xiaoxue; Li, Meng; Sun, Wenjie; Fu, Wei (Frontiers in Nuclear Medicine, 2022)
Purpose: To calculate the physiological uptake of various tissues in 18F-FAPI-04 and 18F-FAPI-42 PET/CT in cancer patients and to compare the variation of standard uptake values between the two scans. Material and methods: This retrospective analysis included 40 cancer patients who underwent 18F-FAPI; 20 each received 18F-FAPI-04 PET/CT and 18F-FAPI-42 PET/CT, respectively. Forty-nine normal tissues including the brain (cerebrum/cerebellum), parotid and submandibular glands, palatine tonsils, and thyroid were identified on CT images. Median SUVmax and SUVmean were calculated for these normal tissues. We also compared the SUVmean of identical tissue to explore the difference of biodistribution in two radiotracers. Results: The accumulation of 18F-FAPI-04 and 18F-FAPI-42 show an analogous pattern. The gallbladder, uterus, submandibular gland, and renal pelvis exhibited the high uptake of two radiotracers (range: SUVmax, 4.01–5.75; SUVmean, 2.92–4.22). Furthermore, bony uptake was slightly higher in 18F-FAPI-42 than 18F-FAPI-04 (range: SUVmean, 0.4±0.22–0.9±0.34; 0.3±0.24–0.7±0.18, respectively, P<0.05), while some soft tissues presented a higher uptake of 18F-FAPI-04 than 18F-FAPI-42 (range: SUVmean, 0.9±0.24–1.5±0.35; 0.9±0.26–1.2±0.37, respectively, P<0.05). Conclusion: Both radioligands exhibited similar physiological uptake of normal tissues in cancers patients. In addition, 18F-FAPI-42 showed lower uptake of soft tissues than 18F-FAPI-04, but demonstrated higher bony uptake than 18F-FAPI-04.